A Watchful Eye: A Case Report on The Management of Hypotony Maculopathy after Non-Valved Glaucoma Drainage Device Implantation: Poster Presentation - Case Report - Resident - Herdian, Felicia Sesih; Amanda, Lia; Ivanovna, Regina; Gunardi, Triana Hardianti; Yunard, Ardiella; Suryono, Astrianda Nadya (Majalah Oftalmologi Indonesia, 2023)
Introduction : Low intraocular pressure (IOP) and reduced visual acuity following glaucoma surgery have been linked to a serious complication known as hypotony maculopathy. Here, we report a case of hypotony maculopathy following glaucoma drainage implant which was successfully managed by a conservative approach utilizing oral and topical steroids, resulting in favorable outcomes. Case Illustration : A 25-year-old female with juvenile glaucoma presented with low IOP in the right eye (RE) following glaucoma drainage surgery using non-valved implant four months prior. Ophthalmic examination revealed a decrease of IOP (9mmHg to 4mmHg) and visual acuity (6/6 to 6/24). Fundus examination and optical coherence tomography (OCT) of macula was indicating hypotony maculopathy. All glaucoma medications were discontinued and the patient was given oral methylprednisolone 3x8 mg and topical prednisolone acetate three hourly for two months. Subsequent follow-up revealed an increase in IOP to 37mmHg and visual acuity improvement to 6/6. The patient was then given oral and topical antiglaucoma medications to maintain IOP control. Discussion : Hypotony and its related sequelae are more common with the non-valved drainage devices. Prompt intervention is crucial for improving visual outcomes. Treatment options include surgical and conservative approach. Closely monitored conservative therapy may also give favorable outcomes similar to surgical approach. Conclusion : In advanced cases of glaucoma, extremely low IOP is just as risky as a high IOP. Conservative therapy, including topical and oral corticosteroids, can be employed to reverse hypotony, at the expense of transient IOP rise, in corticosteroid-responsive patients. Restoring normal IOP in a timely manner may improve retinal function.